THE INFLUENCE OF THE SUPERVISOR’S TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL JUSTICE ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT OF THE EMPLOYEES OF THE BANK FOR AGRICULTURE AND AGRICULTURAL COOPERATIVES HEAD OFFICE - เฉลียวเกรียงไกร, สาลี; นะมิ, มาเรียม; ชูสนุก, อัมพล (RMUTT Global Business and Economics Review, 2016)
The objectives of this research were to develop and validate causal relationship model of supervisor’s transformational leadership and organizational justice on job satisfaction and the organizational commitment of employees of the bank for agriculture and agricultural cooperatives head office (BAAC) with empirical data. The researchers used quantitative methods which involved empirical research. The instrument of this research was a questionnaire used to collect data from 399 employees from BAAC head office. It was found that (1) Supervisor’s transformational leadership had positive and direct influence on employee’s job satisfaction; (2) Supervisor’s transformational leadership had positive and direct influence on organizational commitment; (3) Organizational justice in the dimension of distributive justice had positive and direct influence on job satisfaction; (4) Organizational justice in the dimension procedural justice had positive and direct influence on job satisfaction; (5) Organizational justice in the dimension of Interactional justice had not influence on job satisfaction; (6) Organizational justice in the dimension of distributive justice had positive and direct influence on organizational commitment; (7) Organizational justice in the dimension of procedural justice had not influence on organizational commitment; (8) Organizational justice in the dimension of Interactional justice had not influence on organizational commitment and (9) Job satisfaction had positive and direct influence on organizational commitment.